2023
DOI: 10.1055/a-2021-8910
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants in the Very Elderly

Abstract: No Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…7 A shared-decision making approach is encouraged between physicians and patients to individualize and optimize OAC therapy strategies (including dosage regimen) based on their comorbidities, comedications, values, and preferences. 7,30,31,37 This study had several strengths. The CPRD, shown to be representative of the general UK population, allowed us to assemble a large, well-defined study population of 47 242 very elderly patients with incident NVAF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A shared-decision making approach is encouraged between physicians and patients to individualize and optimize OAC therapy strategies (including dosage regimen) based on their comorbidities, comedications, values, and preferences. 7,30,31,37 This study had several strengths. The CPRD, shown to be representative of the general UK population, allowed us to assemble a large, well-defined study population of 47 242 very elderly patients with incident NVAF.…”
Section: Discussionmentioning
confidence: 99%
“…30 Therefore, which DOAC should be preferentially prescribed to these patients is uncertain. 30,31 Two cohort studies compared the effectiveness and safety of apixaban, rivaroxaban, and dabigatran in patients with NVAF older than 80. 17,18 In line with previous findings from observational studies in younger populations, one of these studies suggested that apixaban was at least as effective as dabigatran and rivaroxaban and was associated with a lower major bleeding risk in patients with NVAF over 80.…”
Section: Discussionmentioning
confidence: 99%
“… 125 Importantly, when using a DOAC in elderly patients with AF, adequate dosing as per the drug label should be chosen to avoid unnecessary complications. 126 …”
Section: Special Situationsmentioning
confidence: 99%
“…Tailored dosing strategy including information about genotype and the concomitant use of interacting drug(s), may reduce variability in drug levels, thereby improving clinical outcomes. 3 The issue of polypharmacy, typically defined as the concomitant use of five or more medications, is indeed particularly relevant in elderly patients with AF, often associated with multiple health conditions, falls, frailty, and dementia. The study from Grymonprez et al 4 confirmed worse outcomes including increased bleeding and mortality risks associated with polypharmacy.…”
Section: Working Against the Clot Anticoagulation Managementmentioning
confidence: 99%
“…Tailored dosing strategy including information about genotype and the concomitant use of interacting drug(s), may reduce variability in drug levels, thereby improving clinical outcomes. 3…”
Section: Working Against the Clotmentioning
confidence: 99%